Transvaginal Management of Vaginal Cuff Dehiscence with Bowel Evisceration following Delayed Diagnosis - Samantha Bleull; Hunter Smith; Robert Shapiro (Case Reports in Obstetrics and Gynecology)
One of the most serious complications that can arise from hysterectomy is vaginal cuff dehiscence with subsequent bowel evisceration. Treatment via vaginal approach has been utilized in early cases of vaginal cuff dehiscence where the need for bowel resection is less likely. Our case examines the treatment of vaginal cuff dehiscence through a vaginal approach approximately 36 hours after apparent vaginal dehiscence with subsequent bowel evisceration. In this case, we chose a vaginal approach even in the setting of possible bowel obstruction and a significant leukocytosis. We utilized CT scan findings to help guide our surgical approach. Although the subjective appearance of the bowel protruding through the vaginal cuff was reassuring, this played little role in guiding our decision with regard to surgical approach. Vaginal cuff dehiscence with evisceration can be managed successfully via a vaginal approach even with prolonged exposure of the bowel to vaginal flora. CT scan should be utilized to evaluate bowel integrity when considering a vaginal dehiscence repair. A high index of suspicion is warranted as these cases can present up to many years after hysterectomy.